Optimalisasi Sistem Informasi Manajemen Dalam Mendukung Efisiensi Dan Daya Saing Bisnis Di Era Digital - Muhammad Sabil Ahror; Aulio yuda prasetya; Rahmawati; Citra Anisa Tika Putri (GLOBAL SCIENTS PUBLISHER, 2025)
Management Information System (MIS) is an integral part of data and information management that supports strategic decision-making processes within organizations. In today’s digital era, MIS functions not only as an administrative tool but also as a catalyst for business transformation. This study aims to analyze the general application of MIS and examine a case study of its implementation at PT Telkom Indonesia Tbk. This research employs a qualitative descriptive method through literature studies and documentation. The results indicate that an integrated MIS improves operational efficiency, accelerates information flow, and supports service innovation. The case study of Telkom Indonesia emphasizes that MIS is a key foundation in enabling digitalization, efficiency, and competitiveness in the telecommunications industry.